Iron(III)‐Catalyzed Denitration Reaction: One‐Pot Three‐Component Synthesis of Imidazo[1, 2‐a]pyridine Derivatives. Issue 13 (11th March 2014) - Yan, Hao; Wang, Yuling; Pan, Congming; Zhang, Hao; Yang, Sizhuo; Ren, Xiaoyu; Li, Jian; Huang, Guosheng
Abstract: An iron(III)‐catalyzed one‐pot three‐component cross‐coupling nitration reaction of 2‐aminopyridines, aldehydes and nitroalkanes, straightforwardly forms imidazo[1, 2‐ a ]pyridine derivatives and is described in this report. The system shows good functional‐group tolerance and proceeds smoothly in moderate to good yields. Abstract : An iron(III)‐catalyzed one‐pot three‐component cross‐coupling nitration reaction of 2‐aminopyridines, aldehydes, and nitroalkane, leading to the straightforward formation of imidazo[1, 2‐ a ]pyridine derivatives has been reported. In this procedure, the starting materials are commercially available. The system shows good functional‐group tolerance and proceeds smoothly in moderate to good yields.